AI and Employee Well-Being: Assessing the Ethical Implications of AI-Driven Human Resource Practices in Indian Universities - Thakur, R. A.; Talukdar, Mitali; Iyer, Sailesh; Liu, Ling-Chun; Chen, Chin-Ling; Singh, Anju (Journal of Ecohumanism, 2025)
The advent of Artificial Intelligence (AI) in Human Resource (HR) practices is fundamentally transforming the management of talent and the optimization of workforce efficiency, particularly in the context of Indian universities. As AI-driven systems increasingly shape HR decisions, there is a pressing need to evaluate their impact on employee well-being, a crucial yet often overlooked aspect. This research paper provides a critical analysis of the ethical implications associated with the deployment of AI in HR practices within Indian academic institutions, with a specific focus on employee well-being. The study investigates key areas where AI is being utilized, including talent acquisition, performance assessment, and employee surveillance, and assesses how these applications influence the psychological, emotional, and professional well-being of university staff. By incorporating contemporary ethical frameworks and examining case studies from Indian universities, the paper illuminates both the potential benefits of AI—such as personalized employee experiences and efficiency gains—and the significant risks, including bias, privacy concerns, and job security issues. In response to these findings, the research proposes an ethical framework tailored to the Indian higher education context, aimed at guiding the responsible integration of AI into HR practices. This framework emphasizes the prioritization of employee well-being alongside institutional objectives, ensuring a balanced approach to AI adoption. The insights presented in this paper are intended to contribute to the broader discourse on ethical AI implementation in the workplace, offering valuable guidance for HR professionals, policymakers, and AI developers within Indian universities to foster a more humane and equitable work environment.